2017
DOI: 10.1175/jcli-d-16-0333.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Tropospheric Warming in Climate Models and Satellite Data

Abstract: Updated and improved satellite retrievals of the temperature of the mid-to-upper troposphere (TMT) are used to address key questions about the size and significance of TMT trends, agreement with model-derived TMT values, and whether models and satellite data show similar vertical profiles of warming. A recent study claimed that TMT trends over 1979 and 2015 are 3 times larger in climate models than in satellite data but did not correct for the contribution TMT trends receive from stratospheric cooling. Here, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 79 publications
9
61
0
Order By: Relevance
“…MSU2 trends for global means and for the deep tropics (20°N‐S) are included in Table , comparing RSS, STAR, and WACCM ensemble results; while the satellite‐derived trends are systematically smaller than in the model, the statistical uncertainties do overlap at the 2 sigma level, for example, 20°N‐S MSU2 trends for WACCM are 0.23 ± 0.03 K/decade, versus 0.18 ± 0.05 for RSS and 0.21 ± 0.06 for STAR data. We note that our derived observational MSU2 trends for 1979–2014 are slightly larger than results in Mears and Wentz () and Santer et al (), although they overlap within uncertainties; these differences occur because of different details in the regression methodologies. This is discussed further in section 4.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…MSU2 trends for global means and for the deep tropics (20°N‐S) are included in Table , comparing RSS, STAR, and WACCM ensemble results; while the satellite‐derived trends are systematically smaller than in the model, the statistical uncertainties do overlap at the 2 sigma level, for example, 20°N‐S MSU2 trends for WACCM are 0.23 ± 0.03 K/decade, versus 0.18 ± 0.05 for RSS and 0.21 ± 0.06 for STAR data. We note that our derived observational MSU2 trends for 1979–2014 are slightly larger than results in Mears and Wentz () and Santer et al (), although they overlap within uncertainties; these differences occur because of different details in the regression methodologies. This is discussed further in section 4.…”
Section: Resultssupporting
confidence: 85%
“…Global average tropospheric warming, as measured by observed 1979–2014 trends in MSU2, is somewhat smaller than corresponding MSU2 trends simulated by WACCM, although the differences are not statistically significant (Table ). These observed versus model differences for MSU2 are similar to previous results based on comparisons with other climate models (Santer et al, , and references therein), although our comparisons reveal only statistically insignificant trend differences for the forced WACCM simulations. The excellent agreement for WACCM is at least partly attributable to forcing using observed SSTs, which tightly constrain tropospheric temperatures, as compared to free‐running atmosphere‐ocean climate models (e.g., CMIP5).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…They demonstrated a major improvement in signal to noise going from ten year to 32 years trends, and concluded that a minimum of seventeen years was required for identification of human effects on temperature. Subsequently Santer et al (2017) analysed the middle troposphere satellite record for the time period used here, concluding that the claim of no significant tropospheric warming over the last eighteen years is not correct. What is concluded in those analyses reinforces the conclusions reached here about the inappropriateness, in the face of internal climate variability, of trying to evaluate anthropogenic contributions to global temperature using truncated temperature data sets.…”
Section: Discussionmentioning
confidence: 99%